2008
DOI: 10.1145/1371574.1371575
|View full text |Cite
|
Sign up to set email alerts
|

A framework for simulation of surrounding vehicles in driving simulators

Abstract: This article describes a framework for generation and simulation of surrounding vehicles in a driving simulator. The proposed framework generates a traffic stream, corresponding to a given target flow and simulates realistic interactions between vehicles. The framework is based on an approach in which only a limited area around the driving simulator vehicle is simulated. This closest neighborhood is divided into one inner area and two outer areas. Vehicles in the inner area are simulated according to a microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…This was important in order for the test leader to have the subject focus on the research related questions that were separate from the experience of driving a simulator vehicle, in our case, the surrounding traffic. Secondly, the questions in the post-questionnaire have been used in previous studies in the same simulator, hence allowing us to confirm that the driving experience in the present study did not deviate in a significant way from other simulator studies performed (Janson Olstam, 2005;Janson Olstam et al, 2008). If it was concluded that the drive was normal regarding the simulator experience, we could leave that aspect of the study and focus on the research questions at hand.…”
Section: Post-questionnaire and Interviewsupporting
confidence: 60%
See 4 more Smart Citations
“…This was important in order for the test leader to have the subject focus on the research related questions that were separate from the experience of driving a simulator vehicle, in our case, the surrounding traffic. Secondly, the questions in the post-questionnaire have been used in previous studies in the same simulator, hence allowing us to confirm that the driving experience in the present study did not deviate in a significant way from other simulator studies performed (Janson Olstam, 2005;Janson Olstam et al, 2008). If it was concluded that the drive was normal regarding the simulator experience, we could leave that aspect of the study and focus on the research questions at hand.…”
Section: Post-questionnaire and Interviewsupporting
confidence: 60%
“…where v DS is the current speed of the driving simulator,v des DS is the estimated desired speed of the simulator driver (estimated according to the procedure described in Janson Olstam et al (2008)). The parameter α is a weighting factor based on the distance to the second trigger point calculated as…”
Section: Estimation Of the Start Time Of A Playmentioning
confidence: 99%
See 3 more Smart Citations